2008
DOI: 10.1021/jo702681e
|View full text |Cite
|
Sign up to set email alerts
|

Metalated Nitriles:  Internal 1,2-Asymmetric Induction

Abstract: Alkylations of conformationally constrained acyclic nitriles containing vicinal dimethyl groups and an adjacent phenyl group or trisubstituted alkene are exceptionally diastereoselective. Probing the alkylation stereoselectivity with a series of C- and N-metalated nitriles implicates a reactive conformation in which an sp2-hybridized substituent projects over the metalated nitrile to avoid allylic strain. Steric screening thereby directs the electrophilic attack to the face of the metalated nitrile opposite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…5−10 Fleming and co-workers discussed the stereochemical aspects of αlithiation and α-magnesation of nitriles with strong bases. 6,11 In an early report Rappoport and co-workers described the utilization of a large excess of tetraethylammonium fluoride to generate cyanmethide carbanions from acetonitrile and use them in Michael addition reactions. 12 An example making use of the bifunctional reactivity of Ru-and Ir-based amido complexes to activate α-substituted α-cyano acetates was reported by Ikariya and co-workers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5−10 Fleming and co-workers discussed the stereochemical aspects of αlithiation and α-magnesation of nitriles with strong bases. 6,11 In an early report Rappoport and co-workers described the utilization of a large excess of tetraethylammonium fluoride to generate cyanmethide carbanions from acetonitrile and use them in Michael addition reactions. 12 An example making use of the bifunctional reactivity of Ru-and Ir-based amido complexes to activate α-substituted α-cyano acetates was reported by Ikariya and co-workers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The same applies for previously reported transition-metal-catalyzed Michael addition reactions, therefore significantly limiting the substrate scope. The reaction usually involves C–H activation at the α-carbon at the metal center to generate the Michael donor moieties (i.e., metal stabilized carbanions). Fleming and co-workers discussed the stereochemical aspects of α-lithiation and α-magnesation of nitriles with strong bases. , In an early report Rappoport and co-workers described the utilization of a large excess of tetraethylammonium fluoride to generate cyanmethide carbanions from acetonitrile and use them in Michael addition reactions . An example making use of the bifunctional reactivity of Ru- and Ir-based amido complexes to activate α-substituted α-cyano acetates was reported by Ikariya and co-workers …”
Section: Introductionmentioning
confidence: 99%
“…To verify the viability of such a proposal, we decided to study the alkylation of 2-alkyl-2-[(2-p-tolylsulfinyl)phenyl]acetonitriles 3 (Scheme 1) under different conditions, which would provide a ready access to the a,a-dialkylphenylacetonitrile fragment, present in biologically active molecules, in either of its two possible configurations. Compounds 3, with intermediate structures between those of 1 and 2, were chosen for this study because marked conformational constrains of differently metalated nitriles have been reported recently as responsible for their stereodivergent evolution in intramolecular [13] and intermolecular [14] alkylation processes. Results obtained in this study are herein reported.…”
Section: Introductionmentioning
confidence: 99%
“…69 Embedding vicinal methyl groups in an alkyl chain containing a trisubstituted alkene, or a benzene ring, creates a strong bias for the stereoselective installation of quaternary stereogenic centers (Scheme 52). 70…”
Section: Enantioselective Alkylation Diastereoselective Alkylations W...mentioning
confidence: 99%